Trefoil factors peptide-3 is associated with residual invasive breast carcinoma following neoadjuvant chemotherapy - Suhail Al-Salam (BMC Cancer, 2019)
Abstract Background Breast carcinoma is the commonest cancer among UAE population and the most common cancer among females. Examination of the 5′ promoter regions of trefoil factor 3 (TFF3) gene has identified putative estrogen and progesterone receptor–DNA binding domains as direct response elements to estrogen and progesterone that are linked to breast functions or steroid regulation. The study was designed to determine the role of TFF3 in breast cancer chemoresistance with the aim of establishing TFF3 expression as a biomarker for drug resistance. Methods In total, 133 cases of breast carcinoma treated with neo-adjuvant therapy were collected. Tissue samples from pre-neoadjuvant therapy as well as tissues from post-neo-adjuvant therapy of those cases were collected and stained with immunohistochemistry for TFF3, Bcl2, BAX, cleaved caspase-3, AKT-1, NF kappa B and Ki-67. Results There was increased expression of TFF3 in residual invasive carcinoma cells. There was a significant correlation between the expression of TFF3 in breast carcinoma cells and response to neoadjuvant chemotherapy (p = 0.0165). There was significant co-expression of TFF3 with AKT1 (p = 0.0365), BCl2 (p = 0.0152), and NF Kappa-B (p = 0.0243) in breast carcinoma cases with residual carcinoma following neoadjuvant therapy which support the role of TFF3 in chemoresistance. Conclusion The expression of TFF3 is significantly associated with residual breast carcinoma following neoadjuvant chemotherapy suggesting its expression is associated with increased resistance to chemotherapy. This is supported by its co-expression with antiapoptotic proteins; BCl2, AKT1 and NF Kappa-B in residual breast carcinoma cells and very low proliferating index and apoptotic bodies in residual tumors.